Granulomatosis with Polyangiitis (Wegener Granulomatosis) Mimicking Infective Endocarditis - Imène Rachdi; Lilia Baili; Fatma Daoud; Zohra Aydi; Hana Zoubeidi; Basma Ben Dhaou; Fatma Boussema (European Journal of Case Reports in Internal Medicine, 2014)
Introduction Infective endocarditis (IE) has been reported to mimic granulomatosis with polyangiitis (GPA) and to test positive to antineutrophil cytoplasmic antibodies (ANCA), which may lead to a misdiagnosis and inappropriate treatment.